2022
DOI: 10.3390/diagnostics12051289
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Related Infections and Their Risk Factors for Treatment Failure—A Major Trauma Centre Perspective

Abstract: Fracture related infections (FRI) are debilitating and costly complications of musculoskeletal trauma surgery that can result in permanent functional loss or amputation. Surgical treatment can be unsuccessful, and it is necessary to determine the predictive variables associated with FRI treatment failure, allowing one to optimise them prior to treatment and identify patients at higher risk. The clinical database at a major trauma centre was retrospectively reviewed between January 2015 and January 2021. FRI tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
(91 reference statements)
0
8
1
1
Order By: Relevance
“…We had analyzed 311 cases by taking age, sex, nature of fracture, pattern of fracture, mechanism of injury, follow-up in weeks, nail type, reduction technique and presence or absence of infection as predictors of clinical outcome and in our study we found that the prevalence infection among patients who had long bone fractures and treated with SIGN nailing was 4.2%. This finding is higher compared with a study conducted in UK which showed that the overall fractured related infection rate was 1.16% [32]. This might be due to setup difference; developing versus developed countries.…”
Section: Discussioncontrasting
confidence: 66%
“…We had analyzed 311 cases by taking age, sex, nature of fracture, pattern of fracture, mechanism of injury, follow-up in weeks, nail type, reduction technique and presence or absence of infection as predictors of clinical outcome and in our study we found that the prevalence infection among patients who had long bone fractures and treated with SIGN nailing was 4.2%. This finding is higher compared with a study conducted in UK which showed that the overall fractured related infection rate was 1.16% [32]. This might be due to setup difference; developing versus developed countries.…”
Section: Discussioncontrasting
confidence: 66%
“…Moreover, it is comparable with the 10%-11% reported on PJIs. [36][37][38][39] Both of those patients with polymicrobial infections were obese, which is a documented risk factor for presenting polymicrobial infections and for FRI treatment failure. 40 The main limitation of this study is related to its design.…”
Section: Discussionmentioning
confidence: 99%
“…3 a). As far as mentioned above, High-energy traumas may cause open fractures that may lead to fracture-related infections (FRI) [ 40 , 41 ]. Also, it has been reported that the vast majority of the cases of bone infections are due to different types of Staphylococcus aureus as a gram-positive bacteria [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…There can be permanent functional loss or amputation from fracture-related infections (FRIs). Additionally, open flaps can cause sepsis as a serious life-threatening consequence in severe cases [ 40 , 41 ]. Also, infections can deteriorate the bone healing process and delay it.…”
Section: Introductionmentioning
confidence: 99%